THE INTERCONNECTION BETWEEN EMOTIONAL INTELLIGENCE AND SOCIAL STEREOTYPES AMONG EDUCATION PROFESSIONALS - LACHINYAN, LILIT; MAJDALANY, DAYANA; GHAZARIAN, MARY (KATCHAR / ACADEMIA. SOCIAL SCIENCE PERIODICAL, 2025)
The article presents the results of a psychological study conducted with professionals working in the Lebanese educational system, with a particular emphasis on the interaction between social stereotypes and emotional intelligence. It sheds light on the importance of social skills to build relationships inside classrooms and improve the quality of the teaching and learning process. The study highlights the negative impact of social stereotypes encountered in pedagogical institutions, which adversely affect the quality, equity, and effectiveness of education. The connection between emotional intelligence and social stereotypes has been identified both among educators working in educational institutions and among students. This study explores in depth how stereotypes—particularly those related to age and professional roles—undermine educational equity and quality. Findings reveal a significant inverse correlation between emotional intelligence and the tendency to rely on such stereotypes. Educators with higher emotional intelligence are more likely to recognize individual differences, manage their own biases, and foster inclusive, empathetic classroom environments. The research underscores the critical role of emotional intelligence in reducing stereotype-based thinking and enhancing pedagogical effectiveness. Based on a thorough analysis of the research findings, the article provides practical recommendations and guidelines for educational institutions and educators aimed at combating social stereotypes within pedagogical environments. These recommendations focus on teacher training and institutional reforms designed to cultivate emotionally intelligent educators, thereby promoting more equitable and socially just educational practices. Keywords: Social stereotypes, social skills, emotional intelligence, pedagogue, educational system.